An Unexpected Presentation of Serotonin Syndrome in a Patient Receiving ECT - Shahzaib Khan; Breanna Wennberg; Malgorzata Witkowska; Jacob Rattin; Raunak Khisty (Case Reports in Psychiatry)
Serotonin syndrome is a toxidrome consisting of autonomic instability, altered mentation, hyperreflexia, clonus, and seizures. It is suspected to be due to either elevated serotonin concentrations or overstimulation of 5-hydroxytryptamine (5-HT) receptors. There are at least seven families of serotonin or 5-HT receptors along with multiple subtypes. The 5-HT1A and 5-HT2A serotonin receptor subtypes are heavily suspected to cause the broad spectrum of symptoms seen in serotonin syndrome. We present the case of a young woman treated with multiple psychotropic medications who developed serotonin syndrome (SS) after receiving electroconvulsive therapy (ECT). She had multiple psychiatric hospitalizations, and ECT was determined to be the appropriate course of treatment due to her treatment-resistant symptoms and catatonia. The case was unique as she tolerated multiple ECT treatments over a few weeks before the acute onset of serotonin syndrome following her eighth treatment, and she did not have any medication changes after the second ECT treatment. The patient’s acute presentation of rigidity, elevated temperature, hyperreflexia, diaphoresis, confusion, and psychomotor agitation led to a diagnosis of serotonin syndrome. ECT is a neuromodulatory procedure approved for treatment-resistant depression and schizophrenia that involves electrically stimulating the brain with electrodes on the scalp to induce a seizure. The mechanism by which ECT confers therapeutic benefit for patients with neuropsychiatric conditions is not entirely understood. We discuss some of the literature on SS and ECT to better understand the potential for a causal relationship.